2005
DOI: 10.1681/asn.2004121055
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Concentration Specifies Differential Signaling Profiles of Growth Arrest/Differentiation and Apoptosis in Podocytes

Abstract: Podocyte depletion occurs in most progressive glomerular diseases and is thought to result from podocyte loss while the remaining podocytes are unable to proliferate. The underlying mechanisms for podocyte growth arrest/differentiation and depletion remain poorly understood but may involve TGF-␤, which is typically upregulated in injured glomeruli. The TGF-␤ are multifunctional cytokines that regulate growth, differentiation, and apoptosis in most cells. Determinants of functional specificity of TGF-␤ signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 43 publications
6
102
0
Order By: Relevance
“…4 Levels of cyclin D1, a critical promoter of early cell-cycle progression in G1/S phase, were considerably increased in DKO and absent in CKO, compared with WT podocytes ( Figure 4E). Protein and mRNA levels of the cyclin-dependent kinase inhibitor (cdki) p15…”
Section: Receptor-regulated Smad2 and Smad3mentioning
confidence: 95%
See 3 more Smart Citations
“…4 Levels of cyclin D1, a critical promoter of early cell-cycle progression in G1/S phase, were considerably increased in DKO and absent in CKO, compared with WT podocytes ( Figure 4E). Protein and mRNA levels of the cyclin-dependent kinase inhibitor (cdki) p15…”
Section: Receptor-regulated Smad2 and Smad3mentioning
confidence: 95%
“…Autocrine and paracrine TGF-␤ induces G0/G1 arrest in podocytes in a Smad3-dependent manner. 4 To examine the relative roles of Smad2/3 and CD2AP in baseline and TGF-␤-stimulated growth regulation of podocytes, we quantified growth rates of WT, DKO, and CKO podocytes using tetrazolium salt WST-1-based proliferation assays as described previously. 28 Growth of untreated CKO cells was significantly reduced compared with WT podocytes, whereas untreated DKO podocytes proliferated at a significantly increased rate ( Figure 4A).…”
Section: Receptor-regulated Smad2 and Smad3mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, p38 signalling can contribute to proinflammatory and profibrotic responses. Activation of p38 enhances production of monocyte chemoattractant protein-1 (MCP-1) by vascular endothelial cells [23], induces local angiotensinogen production in rat tubular cells [17], stimulates both TGF-β-induced fibronectin accumulation in renal interstitial fibroblasts [24] and collagen production in mouse mesangial cells [25], increases Tgf-β1 (also known as Tgfb1) expression in renal tubular cells [26] and promotes synthesis of vascular endothelial growth factor induced by angiotensin II [27,28]. Studies have also shown that p38 signalling mediates both tubular hypertrophy induced by high glucose [26] and transactivation of the epidermal growth factor receptor required for dedifferentiation of proximal tubular epithelial cells following oxidant injury [29].…”
Section: Introductionmentioning
confidence: 99%